Influence of 3D Printing Parameters on the Mechanical Properties for Numerical Simulation of the Poly (Lactic Acid) - Catana, Dorin; Brus, Denisa Iulia; Pop, Mihai Alin; Luca, Mihai Alexandru (Polymers, 2025)
Additive manufacturing is a relatively new and modern technological process that is still under development and progress, with a wide range of materials. This study presents the evolution of the mechanical properties of poly (lactic acid) depending on the main parameters of additive manufacturing: speed, infill density, and temperature. In this study, the range considered for each parameter is the one commonly used in printing activities. The study shows that within the analysed range, the relationship between the property values and printing temperature is expressed through third-degree polynomial equations, regardless of the infill density. This study also presents the evolution of the properties as a function of two printing parameters, specifically temperature and infill density. Through statistical analysis, equations were determined that describe the relationship between the studied properties and the printing parameters. The existence of these equations facilitates their integration into commonly used simulation programs for design. Additionally, this study presents the results of the simulation process for tensile tests on additively manufactured structures, based on data obtained from tensile tests. The simulation results show that the outcomes align with those from the tests, and the identified errors can be kept under control.
Keywords: additive manufacturing; poly (lactic acid); mechanical properties; printing parameters; numerical simulation